2020
DOI: 10.1021/acscatal.0c01992
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Effects on the Surface Chemistry of Small Oxygenates on Molybdenum Trioxide

Abstract: Understanding surface reactions of biomass-derived oxygenates on metal oxides is important for designing catalysts for valorization of biomass. This work elucidated the effect of different pretreatments on molybdenum trioxide (MoO3) to understand how surface reactivity is controlled by the surface oxidation state. The catalyst was pretreated in oxidative, inert, and reducing environments. The inert and reducing pretreatments created oxygen vacancies on the catalyst surface that acted as active sites for the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 113 publications
2
13
0
Order By: Relevance
“…The earlier mentioned recent LaMnO 3 nanoparticle-based study occurred at >500 K and proposed that a labile non-stoichiometric oxygen species was involved in the highest activity sites . In various previous reports, low-temperature crotonaldehyde formation (<500 K) has been observed in the absence of oxygen vacancies on metal oxides, while a high-temperature crotonaldehyde formation mechanism (>500 K) has been observed in the presence of oxygen vacancies. , For the present study, based on crotonaldehyde only being observed at temperatures >500 K and with a very small <1% yield, we infer that the crotonaldehyde formation occurs by aldol addition with one vacancy or with a pair of vacancies. , The presently known pathways for crotonaldehyde produced by aldol addition, involving either one vacancy or a pair of vacancies, are shown in Figure , along with a pathway to acetone formation being proposed in this study. An intermediate labeled as “I C ” is shown in the newly proposed path to acetone (Figure ).…”
Section: Results and Discussionsupporting
confidence: 51%
“…The earlier mentioned recent LaMnO 3 nanoparticle-based study occurred at >500 K and proposed that a labile non-stoichiometric oxygen species was involved in the highest activity sites . In various previous reports, low-temperature crotonaldehyde formation (<500 K) has been observed in the absence of oxygen vacancies on metal oxides, while a high-temperature crotonaldehyde formation mechanism (>500 K) has been observed in the presence of oxygen vacancies. , For the present study, based on crotonaldehyde only being observed at temperatures >500 K and with a very small <1% yield, we infer that the crotonaldehyde formation occurs by aldol addition with one vacancy or with a pair of vacancies. , The presently known pathways for crotonaldehyde produced by aldol addition, involving either one vacancy or a pair of vacancies, are shown in Figure , along with a pathway to acetone formation being proposed in this study. An intermediate labeled as “I C ” is shown in the newly proposed path to acetone (Figure ).…”
Section: Results and Discussionsupporting
confidence: 51%
“…In detail, 22.2 mmol of ZrO(NO 3 ) 2 •6H 2 O and 8.9 mmol of Cu(NO 3 ) 2 •3H 2 O were simultaneously put into 200 mL of ethanol for the dissolution under ultrasound assistance for 30 min, and then, oxalic acid dihydrate (31.0 mmol) was quickly added with magnetic stirring at room temperature (RT). After 2 h stirring, the obtained precipitate was transferred into a 250 mL Teflon-lined autoclave followed by aging at different temperatures (20,50,90,110, and 130 °C) for 10 h. The product was dried at 90 °C for 6 h, followed by reducing in the atmosphere of 10% H 2 /N 2 at 500 °C for 3 h with a ramp rate of 10 °C•min −1 . The resulting reduced sample was denoted as CZ-20, CZ-50, CZ-90, CZ-110, and CZ-130.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to metal, the influence by the type and composition of the support on catalytic behavior should not be ignored. Even with the same type and composition, the support with different defect structures could also have significant impact on the catalytic behavior. , Catalyst supports with oxygen vacancies exhibit the promotional effect on the CO dissociation and alcohol dehydrogenation. For example, Liu and co-worker reported that Cu/ZrO 2 containing abundant oxygen vacancies show strong adsorption capacity for reactants and hydrogen donors, thus facilitating the CO bond hydrodeoxygenation of lauric acid to lauryl alcohol. In addition, the metal vacancies have been proved to be favorable for the dissociation O–H furthermore as it has been reported that the dissociation energy of the C–OH bond can be greatly reduced after deprotonation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the white lines of the L 2,3 spectra often reveal a split structure due to crystal field effects. Sensitivity of the white line shape to the crystal field, and, therefore, to the symmetry of the local environment, was successfully applied to the analysis of phase composition and local coordination in many Mo-based compounds. ,, Since EXAFS studies at these edges are impossible due to the vicinity of the 2p 1/2 and 2p 3/2 levels, L 2,3 -edge spectroscopy cannot fully replace the spectroscopic investigations at the K-edge. Nice examples for a complementary K- and L-edge analysis can be found in refs , , , and .…”
Section: Introductionmentioning
confidence: 99%